Mapping data on access to and use of medicines among migrants in Flanders [version 2; peer review: 1 approved, 3 approved with reservations] - Saleh Aljadeeah; Loes Meukens (F1000Research)
Background Migration is a social determinant of health, and migrants often face health inequalities compared to host populations. Migrants are underrepresented in health research in many European countries, including Belgium, which is concerning. The World Health Organization (WHO) developed a comprehensive framework aimed at guiding research on migration and health within the WHO European Region. This study supports evidence-based policymaking among European member states by providing a foundational structure for examining various strategies and methodologies. The framework serves as a catalyst for discussion and critical analysis, contributing to the formulation of a global research agenda on migration and health under WHO’s leadership. Additionally, it outlines key research priorities and offers strategic recommendations to enhance the understanding and response to health issues related to migration. One of these recommendations calls on researchers to “maximise the use of existing data from research and routinely collected data in health information systems”. Objective The overarching aim of our study is to map available sources of datasets about access to and use of medicines among migrant populations, and test if and under which conditions they can be used in research, by taking the case of Flanders, Belgium. Methods This study will involve conducting a focused review to map datasets used for reporting access to and use of medicines among migrants, followed by a qualitative study with key informants; a structured analysis of ethical and legal challenges to be addressed when using the datasets we identified for research; and content description and evaluation of the different identified datasets. Results We assert that the results of our study will help presenting the diverse sources of data about medicines access or use among migrant populations. They will be also used to provide recommendations about enhancing the possibilities of retrieving, and using data, including recommendations for (legal, ethical, methodological) risk mitigation for retrieving and using these data.